Covid-19: Some Institutional Issues of the Socialist Oriented Market Economy and Social Development - Van Dang, Nguyen; Quynh Hoa, Luong (VNU Journal of Science: Policy and Management Studies, 2020)
Difficulties resulting from the Covid-19 epidemic have revealed more clearly the challenges of economic growth and social development in our country. The current dilemma is also posing an urgent need for sustainable solutions that help both the state and citizens accumulate resources to adapt to unpredictable situations in the future. In order to stop the slowdown and promote economic growth, it is impossible not to consider the core dimensions of the socialist-oriented market economy institutions. The paper focuses on analyzing a number of economic institutional challenges, including public ownership, state-owned enterprises, and the legal system. On that basis, the author proposes a number of orientations for institutional innovation towards a more dynamic market economy, a more modern public governance system, in order to achieve social development goals.